Pengaruh Gaya Kepemimpinan Dan Dukungan Organisasi Terhadap Organizational Citizenship Behavior (Perilaku Kewargaan) Pada Anggota PC IPNU-IPPNU Kabupaten Mojokerto - Mohammad Khafid Al Ayyubi; Nur Hidayati; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The objective of this study is to ascertain the effect of Leadership Style and Organizational Support on Organizational Citizenship Behavior of IPNU-IPPNU PC Members in Mojokerto Regency. The research conducted in this study is quantitative a nature methodology, utilizing questionnaire distribution as the chosen technique. The study encompassed a population of 171 individuals, for sampling in the study using the slovin method as many as 63 respondents was selected for the research. The data collected were then subjected to analysis through the utilization of the SPSS version 25 software. The research has met the standards for validity and reliability. The techniques used for analyzing data in this study included conducting classical assumption test, multiple linear regression, hypothesis testing and the assessment of adjusted R square. The variables examined in this research encompassed leadership style and organizational support. The study’s outcomes indicated that both Leadership Style and Organizational Support variables collectively and individually impacted Organizational Citizenship Behavior. Keywords: Organizational Citizenship Behavior, Leadership Style and Organizational Support.